Pengaruh Literasi Keuangan Syariah, Sikap Keuangan Dan Pengelolaan Keuangan Terhadap Kinerja UMKM (Studi Kasus UMKM Sektor Kuliner Di Kecamatan Keritang Kabupaten Indragiri Hilir) - Firayani Firayani; Bambang Kurniawan; Eri Nofriza (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The research aims to determine the influence of sharia financial literacy, financial attitudes and financial management on the performance of MSMEs in the culinary sector in Keritang District, Indragiri Hilir Regency. This research uses quantitative methods with an associative approach, the analytical methods used are descriptive statistics, classical assumption testing, multiple linear analysis and hypothesis testing with the Eviews 12 program. This research data is primary data and secondary data. The data collection technique used a questionnaire and the sample in this research was 77 MSMEs in the culinary sector in Keritang District using a purposive sampling technique. The research results show that the sharia financial literacy variable has a significant effect on the performance of MSMEs, the financial attitude variable has a significant effect on the performance of MSMEs and the financial management variable has a significant effecton the performance of MSMEs, while simultaneous testing shows that there is a positive and significant influence on the performance of MSMEs in Keritang District, Indragiri Hilir Regency.